2018
DOI: 10.1007/s12080-017-0364-x
|View full text |Cite|
|
Sign up to set email alerts
|

Ocean zoning within a sparing versus sharing framework

Abstract: The land-sparing versus land-sharing debate centers around how different intensities of habitat use can be coordinated to satisfy competing demands for biodiversity persistence and food production in agricultural landscapes. We apply the broad concepts from this debate to the sea and propose it as a framework to inform marine zoning based on three possible management strategies, establishing: no-take marine reserves, regulated fishing zones, and unregulated open-access areas. We develop a general model that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…Further, Runting et al 45 found greater biodiversity outcomes from improved management compared to shifting to a landscape-sparing strategy. Similar results were found by Kuempel et al 44 in the marine context where optimal budget allocations were split across enforcement or expansion, but the long-term allocations favored enforcement, and by McGowan et al, 46 who found that small management budgets favor marine protected area establishment, whereas larger budgets favor fisheries management strategies. Even restoration, one of the most extreme forms of management, has been found to produce greater outcomes when carried out alongside or even in place of protected area expansion, 47 which is in contrast to tradition orthodoxies.…”
Section: Guidelines For Achieving Aichi Target 11 Objectivessupporting
confidence: 79%
See 2 more Smart Citations
“…Further, Runting et al 45 found greater biodiversity outcomes from improved management compared to shifting to a landscape-sparing strategy. Similar results were found by Kuempel et al 44 in the marine context where optimal budget allocations were split across enforcement or expansion, but the long-term allocations favored enforcement, and by McGowan et al, 46 who found that small management budgets favor marine protected area establishment, whereas larger budgets favor fisheries management strategies. Even restoration, one of the most extreme forms of management, has been found to produce greater outcomes when carried out alongside or even in place of protected area expansion, 47 which is in contrast to tradition orthodoxies.…”
Section: Guidelines For Achieving Aichi Target 11 Objectivessupporting
confidence: 79%
“…Nearly all analyses that have modeled conservation actions based on different budget allocations have concluded that the optimal decision is largely dependent on three factors: the rate of habitat degradation, the relative costs of actions, and time lags between actions. 11,15,16,44,46,70 It is essential that these components are considered when making decisions, however, they are rarely explicitly and transparently included in the conservation decision process (e.g., costs 71 ) and are not recognized as important within international conservation objectives.…”
Section: Beyond 2020mentioning
confidence: 99%
See 1 more Smart Citation
“…The original formulation of the land sparing-sharing framework omits some complexities, but it can be and already has been modified to incorporate many of these, including spatial configuration and the influence of edge effects [60,61]; the influence of changing diets and reducing food waste [50]; inclusion of some ecosystem services [4,7,50,62]; prediction of the effects of specific public policies [63]; and application to forestry [64,65], urban planning [66][67][68][69] and marine conservation [70]. It is a model, and so all assumptions can be varied and tested.…”
Section: What Does the Model Not Do?mentioning
confidence: 99%
“…The framework is now being used in a broader context to encompass issues about landscape design in general, and not just specifically about maximising yield, for example the design of cities and plantation landscapes, livestock production, and fisheries production (e.g. Lin & Fuller 2013; Edwards et al 2014; Law et al 2016; McGowan et al 2018). As its application moves into more general usage the issue of oversimplification becomes even more apparent, emphasizing that limiting landscape decisions to two states (shared or spared) is often too simplistic to produce viable landscape design options.…”
Section: Introductionmentioning
confidence: 99%